PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN SEKRETARIAT NASIONAL PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA - Superyana; Drs. Widodo MM (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
This study aims to analyze the effect simultaneously and partially between compensation and motivation on employee performance at the National Secretariat for Women Empowerment Head of the Family. The research population is all employees of the National Secretariat for Women Empowerment Head of Family which amounts to 51 people. Sampling technique using saturated sampling technique. The result of the research shows that there is simultaneous influence of variable of compensation and motivation to employee performance of National Secretariat of Women Empowerment Head of Family 0,691, there is partial influence of compensation variable to employee performance 0, and there is partial influence of motivation variable to employee productivity equal to 0,522.